2010
DOI: 10.1016/j.apcatb.2010.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic reduction of CO2 using H2 as reductant over ATaO3 photocatalysts (A = Li, Na, K)

Abstract: ATaO 3 (A = Li, Na, K) compound oxides exhibit photocatalytic activity for the reduction of CO 2 in the presence of H 2. Only CO gas was generated over all samples under photoirradiation. The photocatalytic activity was higher in the order corresponding to KTaO 3 , NaTaO 3 and LiTaO 3 (LiTaO 3 > NaTaO 3 > KTaO 3). The order of the photocatalytic activities was consistent with that of the E g (optical gap) values. After 24 h of photoirradiation, the amount of evolved CO reached 0.42 µmol•g-1 over LiTaO 3. TPD e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(90 citation statements)
references
References 18 publications
(17 reference statements)
2
80
1
2
Order By: Relevance
“…CO was the only gaseous product over all of the samples tested under 200 W Hg-Xe lamp irradiation. [54] LiTaO 3 presented the highest activity for CO yield (0.42 µmol/g in 24 h), and the trend of the photocatalytic activities were consistent with that of the E g (LiTaO 3 > NaTaO 3 > KTaO 3 ). In addition, they also found that the amount of evolved CO gas depended on the amount of chemisorbed CO 2 (as shown in Fig.…”
Section: Tantalatessupporting
confidence: 59%
See 3 more Smart Citations
“…CO was the only gaseous product over all of the samples tested under 200 W Hg-Xe lamp irradiation. [54] LiTaO 3 presented the highest activity for CO yield (0.42 µmol/g in 24 h), and the trend of the photocatalytic activities were consistent with that of the E g (LiTaO 3 > NaTaO 3 > KTaO 3 ). In addition, they also found that the amount of evolved CO gas depended on the amount of chemisorbed CO 2 (as shown in Fig.…”
Section: Tantalatessupporting
confidence: 59%
“…In addition, they also found that the amount of evolved CO gas depended on the amount of chemisorbed CO 2 (as shown in Fig. 2), [54] which meant that the adsorption of CO 2 had an effect on the reduction efficiency of CO 2 . H 2 was used as reductant in this photocatalytic reduction of CO 2 process, whereas other gas reaction systems usually used H 2 O as reductant.…”
Section: Tantalatesmentioning
confidence: 97%
See 2 more Smart Citations
“…The order of CO2 reduction activity on alkaline perovskites (LiTiO3 > NaTiO3 > KTiO3) was also found to correlate to some extent with the measured chemisorption capacity [36]. A screening on several oxides performed by the same research team revealed that, in addition to other basic oxides such as CaO, the activity was surprisingly high using Ga2O3 [37][38].…”
Section: Production Of Co By Light-promoted Co2 Reaction With H2mentioning
confidence: 97%